Double-peaked narrow emission-line galaxies in LAMOST survey. Issue 2 (22nd October 2018) - Wang, M-X; Luo, A-L; Song, Y-H; Shen, S-Y; Feng, S; Wang, L-L; Wang, Y-F; Li, Y-B; Du, B; Hou, W; Guo, Y-X; Kong, X; et al.
ABSTRACT: We outline a full-scale search for galaxies exhibiting double-peaked profiles of prominent narrow emission lines, motivated by the prospect of finding objects related to merging galaxies, and even dual active galactic nuclei candidates as by-product, from the Large Sky Area Multi-object Fiber Spectroscopic Telescope (LAMOST) Data Release 4. We assemble a large sample of 325 candidates with double-peaked or strong asymmetric narrow emission lines, with 33 objects therein appearing optically resolved dual-cored structures, close companions, or signs of recent interaction on the Sloan Digital Sky Survey images. A candidate from LAMOST (J074810.95+281349.2) is also stressed here based on the kinematic and spatial decompositions of the double-peaked narrow emission line target, with analysis from the cross-referenced Mapping Nearby Galaxies at the Apache Point Observatory (MaNGA) survey datacube. MaNGA enables us to constrain the origin of double peaks for these sources, and with the IFU data we infer that the most promising origin of double-peaked profiles for LAMOST J074810.95+281349.2 is the 'Rotation Dominated  + Disturbance' structure.